Aneurysm growth, survival, and quality of life in untreated thoracic aortic aneurysms: the effective treatments for thoracic aortic aneurysms study. (29th November 2021) - Sharples, Linda; Sastry, Priya; Freeman, Carol; Bicknell, Colin; Chiu, Yi Da; Vallabhaneni, Srinivasa Rao; Cook, Andrew; Gray, Joanne; McCarthy, Andrew; McMeekin, Peter; Vale, Luke; Large, Stephen
Abstract: Aims: To observe, describe, and evaluate management and timing of intervention for patients with untreated thoracic aortic aneurysms. Methods and results: Prospective study of UK National Health Service (NHS) patients aged ≥18 years, with new/existing arch or descending thoracic aortic aneurysms of ≥4 cm diameter, followed up until death, intervention, withdrawal, or July 2019. Outcomes were aneurysm growth, survival, quality of life (using the EQ-5D-5L utility index), and hospital admissions. Between 2014 and 2018, 886 patients were recruited from 30 NHS vascular/cardiothoracic units. Maximum aneurysm diameter was in the descending aorta in 725 (82%) patients, growing at 0.2 cm (0.17–0.24) per year. Aneurysms of ≥4 cm in the arch increased by 0.07 cm (0.02–0.12) per year. Baseline diameter was related to age and comorbidities, and no clinical correlates of growth were found. During follow-up, 129 patients died, 64 from aneurysm-related events. Adjusting for age, sex, and New York Heart Association dyspnoea index, risk of death increased with aneurysm size at baseline [hazard ratio (HR): 1.88 (95% confidence interval: 1.64–2.16) per cm, P < 0.001] and with growth [HR: 2.02 (1.70–2.41) per cm, P < 0.001]. Hospital admissions increased with aneurysm size [relative risk: 1.21 (1.05–1.38) per cm, P = 0.008]. Quality of life decreased annually for each 10-year increase in age [–0.013 (–0.019 to –0.007), P < 0.001] and for current smoking [–0.043 (–0.064 to –0.023), P = 0.004]. Aneurysm size was not associated with change in quality of life. Conclusion: International guidelines should consider increasing monitoring intervals to 12 months for small aneurysms and increasing intervention thresholds. Individualized decisions about surveillance/intervention should consider age, sex, size, growth, patient characteristics, and surgical risk. Graphical Abstract: